Automatic and Real-time Processing of Tilt Records for Prediction of Explosions at Semeru Volcano, East Java, Indonesia - Hery Kuswandarto; Muhamad Hendrasto; Masato Iguchi (Indonesian Journal of Physics, 2008)
Eruptive activity of Semeru Volcano, East Java, Indonesia, is characterized by intermittent occurrence of strombolian and vulcanian types in intervals of 15 – 45 minutes. The explosive eruptions accompany explosion earthquakes and tilt changes of ground around the summit crater. Prior to the explosions (16 – 300 s before), gradual upward tilts of the crater side were detected with amounts of 0.3 – 20 nrad. The upward tilts turned to downward after start of explosive eruptions and tilt decreased by 0.7 – 50 nrad for 30 – 70 s. In order to detect the precursory tilt changes in real time automatically by using the tilt record, software coded by Visual Basic was developed. The software receives UDP packet data from A/D converter for the tiltmeter and shows the record on PC display. The software judge stages of volcanic activity (pre-eruption or eruption) based on the tilt change. In a test, 72% of increase in tilts prior to explosions was successfully detected.